EFFECTS OF ADMINISTRATORS’ TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL COMMITMENT OF ART SCHOOL TEACHERS IN SHENYANG, LIAONING PROVINCE - Liu Yuou; Tipanark , Peerapong; Mengman , Pornthep (วารสารวิจัยธรรมศึกษา, 2023)
The objectives of this research were: (1) to study the level of administrators’ transformational leadership, and organizational commitment at art school’s teacher in Shenyang. (2) To investigate the effects of administrators’ transformational leadership on organizational commitment, and (3) to study the guideline/approaches to strengthening teachers’ organizational commitment. The total population of this study included 564 administrative staffs and teachers from schools of art in Shenyang. A stratified random sampling method was used to sample, totaling 300 person which calculated from G8Power program. The instrument for collecting data was a questionnaire. Descriptive statistics and inferential statistics were used to perform data analysis by using statistical software of SPSS and AMOS. Research results revealed that: The level of administrators’ transformational leadership, and teacher’s organizational commitment at art schools in Shenyang were at high level. Administrator’ s tranformational leadership was positively correlated and direct effects on teacher’s organizational commitment, able to predict at statistically significant 92% (p < 0.01). The guideline/ approaches to strengthening teachers’ organizational commitment, school administrators must show leadership in managing the organization in order for their teachers to be happy to have a bond with the organization, such as in the aspect of: basic needs, management support, teamwork, working, and career growth.